PERANCANGAN SISTEM PENJADWALAN KULIAH DAN UJIAN SKRIPSI PROGRAM STUDI SISTEM INFORMASI BERBASIS WEB - Rubiyanto Maku (Universitas Muhammadiyah Gorontalo, 2021)
University of Muhammadiyah Gorontalo is one of universities that are already implementing information system in several activities. These are constraints problems in scheduling the courses : the difficulty of making class schedule based on the willingness to teach, the difficulty of arranging a schedule that does not coincide, the difficulty of checking compliance credits, and delayed thesis exam schedule. In Planning and Scheduling System Lecture, Thesis Studies Program Information System, was using HTML and PHP. Method used here are Waterfall is hallmark craftsmanship of each phase in the waterfall must be completed before proceeding to the next phase. So that, the focus of each phase can be done in maximum of craftsmanship. Tests were performed using a system of black box testing. The results obtained in the research is a list Lecturer, Course List, List Lecture Room, Lecture Timetable and Examination Timetable. The scheduling systemis dynamic which means it can be updated.